2015
DOI: 10.1002/jcb.25260
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Response Protein‐1 Expression by Insulin‐Like Growth Factor‐1 Requires ROS‐Dependent Activation of ERK1/2 and PKB Pathways in Vascular Smooth Muscle Cells

Abstract: Early growth response protein-1 (Egr-1) is a transcription factor that plays an important role in the regulation of several genes implicated in the pathogenesis of cardiovascular disease (CVD) such as atherosclerosis. Insulin-like growth factor-1 (IGF-1), a potent mitogen, is believed to contribute to the development of CVD through the hyperactivation of mitogenic and growth promoting pathways, including the MAPK and PKB pathways, as well as regulation of multiple transcription factors. Reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 58 publications
(90 reference statements)
1
16
1
Order By: Relevance
“…We have shown earlier that CaM/CaMKII pathway mediates MEK/ERK1/2 activation in response to ET‐1 in VSMC (Bouallegue et al, ). Additionally, we and others have observed that the MEK/ERK1/2 pathway plays a key role in Egr‐1 expression induced by several stimuli (Hasan & Schafer, ; Liu, Yu et al, ; Youreva & Srivastava, ). Therefore, we investigated if the attenuation of Ang‐II‐induced Egr‐1 expression due to STIM‐1 and Orai‐1 silencing in VSMC was associated with a change in ERK1/2 phosphorylation.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…We have shown earlier that CaM/CaMKII pathway mediates MEK/ERK1/2 activation in response to ET‐1 in VSMC (Bouallegue et al, ). Additionally, we and others have observed that the MEK/ERK1/2 pathway plays a key role in Egr‐1 expression induced by several stimuli (Hasan & Schafer, ; Liu, Yu et al, ; Youreva & Srivastava, ). Therefore, we investigated if the attenuation of Ang‐II‐induced Egr‐1 expression due to STIM‐1 and Orai‐1 silencing in VSMC was associated with a change in ERK1/2 phosphorylation.…”
Section: Resultsmentioning
confidence: 69%
“…Earlier work has demonstrated that MAP kinase signaling plays a key role in inducing Egr‐1 expression in a wide variety of cell types in response to a large number of stimuli (Liu, Yu et al, ; Stefano, Rossler, Griesemer, Hoth, & Thiel, ; Youreva & Srivastava, ). However, our data demonstrating that siRNA‐induced silencing of either STIM‐1 or Orai‐1 resulted in the suppression of ERK1/2 as well as CREB phosphorylation indicated that Ang‐II‐induced SOCE is crucial to induce ERK and CREB phosphorylation in VSMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to investigate the specific contribution of IGF-1R and EGFR in IGF-1-induced HDAC5 phosphorylation, we used AG1024 and AG1478, highly specific inhibitors of IGF-1R and EGFR tyrosine kinase (TK) activity, respectively. As depicted in Figure 2a 3.2 | IGF-1-induced HDAC5 phosphorylation is not mediated by mitogen-activated protein kinase-dependent pathways IGF-1 has been shown to mediate its physiological responses through the activation of hypertrophic and growth promoting signaling pathways, including the mitogen-activated protein kinase (MAPK) pathway Youreva & Srivastava, 2016). Therefore, we next investigated whether the MAPK pathway was involved in mediating IGF-1-induced HDAC5 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, IGF plays a crucial role in the homeostasis of the extracellular matrix. Indeed, IGF, by stimulating chondrocytes, may be involved in the regulation of proteoglycan synthesis [53,54]. The presence of proinflammatory cytokines during the period of inflammation that occurs after the damage to the vessel walls can interfere with the balance between synthesis and degradation in IGF.…”
Section: Induction Of Restenosis By Igfmentioning
confidence: 99%